2017
DOI: 10.3847/1538-4357/aa74e8
|View full text |Cite
|
Sign up to set email alerts
|

Sagittarius A * High-energy X-Ray Flare Properties during NuStar Monitoring of the Galactic Center from 2012 to 2015

Abstract: Understanding the origin of the flaring activity from the Galactic center supermassive black hole SagittariusA * is a major scientific goal of the NuSTAR Galactic plane survey campaign. We report on the data obtained between 2012 July and 2015 April, including 27 observations on Sgr A * , with a total exposure of 1 Ms. We found a total of 10 X-ray flares detected in the NuSTAR observation window, with luminosities in the range of . With this largest hard X-ray Sgr A * flare data set to date, we studied the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 50 publications
2
25
0
3
Order By: Relevance
“…Also, Revnivtsev et al (2004b) reported about the power-law with Γ = 1.8 ± 0.2 (at the 1 confidence interval) for the Sgr B2 spectrum using the INTEGRAL data collected in the 2003-2004 time interval. Furthermore, the similar slope Γ ∼ 2 was estimated for other GC molecular clouds by the reflected emission (Mori et al 2015;Krivonos et al 2017a) and for the observed Sgr A ★ X-ray flares (Baganoff et al 2001;Porquet et al 2003Porquet et al , 2008Nowak et al 2012;Degenaar et al 2013;Neilsen et al 2013;Barrière et al 2014;Zhang et al 2017).…”
Section: Discussionsupporting
confidence: 82%
“…Also, Revnivtsev et al (2004b) reported about the power-law with Γ = 1.8 ± 0.2 (at the 1 confidence interval) for the Sgr B2 spectrum using the INTEGRAL data collected in the 2003-2004 time interval. Furthermore, the similar slope Γ ∼ 2 was estimated for other GC molecular clouds by the reflected emission (Mori et al 2015;Krivonos et al 2017a) and for the observed Sgr A ★ X-ray flares (Baganoff et al 2001;Porquet et al 2003Porquet et al , 2008Nowak et al 2012;Degenaar et al 2013;Neilsen et al 2013;Barrière et al 2014;Zhang et al 2017).…”
Section: Discussionsupporting
confidence: 82%
“…The XVP uncovered a very bright flare reported by Nowak et al (2012), and provided a large, uniform sample of fainter flares (Neilsen et al 2013(Neilsen et al , 2015. NuSTAR observations have since confirmed that Sgr A*'s X-ray flares can have counterparts at even higher energies (up to ∼ 79 keV; Barrière et al 2014;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 76%
“…Ambitious X-ray campaigns with Chandra, XMM Newton, Swift, and NuSTAR have targeted Sgr A* and shown that its emission is relatively quiescent and has been stable over two decades, punctuated by approximately daily X-ray flares (Baganoff et al 2001;Goldwurm et al 2003;Porquet et al 2003Porquet et al , 2008Bélanger et al 2005;Nowak et al 2012;Neilsen et al 2013Neilsen et al , 2015Degenaar et al 2013; Barrière et al 2014;Mossoux et al 2016;Ponti et al 2015;Yuan & Wang 2016;Zhang et al 2017;Bouffard et al 2019). The quiescent component is well-modeled by bremsstrahlung emission from a hot plasma with temperature T ∼ 7 × 10 7 K and electron density n e ∼100 cm −3 located near the Bondi radius (Quataert 2002;Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests strongly that actual maximal luminosity in our models may increases considerably through the synchrotron radiation in the inner region and we expect the maximal luminosity due to the outer shock exceeds far ∼ 10 35 erg s −1 . On the other hand, an upper limit on the quiescent luminosity of Sgr A* above 10 keV was recently derived to be L X q,10−79keV ≤ 2.9 × 10 34 erg s −1 (Zhang et al 2017). If we regard the minimal luminosity ∼ 10 34 erg s −1 in our models as the quiescent luminosity, the luminosity variation of L > 10 34 erg s −1 occurring at a rate of 25 hrs and L > 10 35 erg s −1 occurring approximately every 5 days in this work is qualitatively compatible with the observed long-term flares of Sgr A*.…”
Section: Time Variations Of the Luminosity And The Shock Locationmentioning
confidence: 99%